The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/pbc.30148
|View full text |Cite
|
Sign up to set email alerts
|

Off‐label and compassionate use of targeted anticancer therapies: The experience of an Italian pediatric cancer center

Abstract: Introduction:In Europe, despite recent advances in clinical development, most of the drugs currently used to treat childhood cancers are adult medicines, prescribed outside of the authorized indication. In this context, a monocentric retrospective cohort analysis was conducted, evaluating pediatric, adolescent, and young adult patients affected by onco-hematologic disease, treated with targeted therapies used off-label or as compassionate use. Methods:The analysis was conducted on 45 patients aged less than or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Креативная хирургия и онкология / Creative Surgery and Oncology 2024;14(1):69-77 нения «вне инструкции» у пациентов со злокачественными новообразованиями (ЗНО) центральной нервной системы (ЦНС) [4]. R. Cenna и соавторы опубликовали результаты моноцентрового ретроспективного когортного анализа, в котором проводилось изучение клинических ситуаций c использованием терапии таргетными препаратами «вне инструкции» и по программам расширенного доступа у 45 пациентов со злокачественными новообразованиями в возрасте до 30 лет в крупном педиатрическом центре Италии [12]. Двадцать пять пациентов из 45 имели онкогематологические заболевания.…”
Section: обзорные статьи / Reviewsunclassified
See 1 more Smart Citation
“…Креативная хирургия и онкология / Creative Surgery and Oncology 2024;14(1):69-77 нения «вне инструкции» у пациентов со злокачественными новообразованиями (ЗНО) центральной нервной системы (ЦНС) [4]. R. Cenna и соавторы опубликовали результаты моноцентрового ретроспективного когортного анализа, в котором проводилось изучение клинических ситуаций c использованием терапии таргетными препаратами «вне инструкции» и по программам расширенного доступа у 45 пациентов со злокачественными новообразованиями в возрасте до 30 лет в крупном педиатрическом центре Италии [12]. Двадцать пять пациентов из 45 имели онкогематологические заболевания.…”
Section: обзорные статьи / Reviewsunclassified
“…Как минимум одна побочная реакция отмечена при использовании 76 % препаратов (n = 22) у пациентов с онкогематологическими заболеваниями, и 43 % препаратов (n = 10), применявшихся у больных с солидными опухолями. Авторы исследования подтвердили частое использование таргетной терапии «вне инструкции» детям с онкологическими заболеваниями, особенно при рецидивах, отмечая при этом то, что данное лечение в большинстве случаев эффективно и переносимо [12]. A. Spini и соавторы, опубликовав результаты систематического обзора и метаанализа ряда клинических испытаний и обсервационных исследований, сообщили о том, что у каждого второго педиатрического пациента (≤18 лет) с солидной опухолью, для лечения которых применялись антиангиогенные препараты в качестве монотерапии, наблюдались серьезные нежелательные явления (НЯ) [7].…”
Section: обзорные статьи / Reviewsunclassified
“…8 In an Italian single-center study describing 45 patients treated with off-label or compassionate use of targeted anticancer therapies, the majority of use was in relapsed or refractory disease, 71% experienced at least one adverse drug reaction, and 52% achieved a complete response. 9 Over the last decade, immune checkpoint inhibition (ICI) has revolutionized the field of medical oncology, and the number of patients with adult malignancies treated with ICI has dramatically increased. 10,11 Retrospective studies and early phase clinical trials have demonstrated ICI to be safe and tolerable in pediatric patients with a variety of malignancies, [12][13][14][15][16][17][18][19][20][21][22][23] including central nervous system tumors.…”
Section: Introductionmentioning
confidence: 99%
“…One study evaluating the off‐label use of targeted therapy in pediatric cancers from 2007 to 2017 observed an overall prevalence of 9.2% 8 . In an Italian single‐center study describing 45 patients treated with off‐label or compassionate use of targeted anticancer therapies, the majority of use was in relapsed or refractory disease, 71% experienced at least one adverse drug reaction, and 52% achieved a complete response 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation